PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA LARISSA AESTHETIC CABANG MAGELANG - Amalia Isnaini Purinda Laksana; Heni Hirawati (Transpublika Publisher, 2022)
The purpose of this study was to examine the effect of price, product quality and service quality on customer loyalty at Larissa Beauty Center Magelang Branch using quantitative research methods. The sample in this study is to use raw data from 50 respondents. How to collects data using a questionnaire. The sampling technique used is non-random sampling, using the criteria selected by the researcher at the time of sampling. Respondents in this study were defined as customers of Larissa Skicare Magelang Branch who bought the product or made two or more transactions. The data analysis technique used in this research is multiple linear regression analysis with the help of SPSS program. The results showed that simultaneously price, product quality and service quality had a significant influence on customer loyalty. The product quality and service quality have a positive and significant effect on customer loyalty, but price has a positive and insignificant effect on customer loyalty. The results of the determination test stated that the percentage of the influence of price, product quality and service on customer loyalty was 72.4% so that the influence of other variables on consumer satisfaction outside this study was 27.6%.